Born Again: Recurrent Hepatic Encephalopathy in an Adult without Cirrhosis - Tom George; Sasidharan Rajesh; Cyriac Abby Philips (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Congenital extrahepatic portosystemic shunt (CEPS) develops between the por-to-mesenteric and systemic veins. The splanchnic venous system drains directly to systemic circulation in this condition. We present a case of an adult onset Type II CEPS presenting with hepatic encephalopathy. The patient underwent PARTO (plug-assisted retrograde transvenous obliteration) and had a significant clinical improvement on subsequent follow-up. Our case highlights the importance of imaging and the role of an interventional radiologist in the management of the condition.